2022
DOI: 10.1093/genetics/iyac085
|View full text |Cite
|
Sign up to set email alerts
|

Defining characteristics and conservation of poorly annotated genes in Caenorhabditis elegans using WormCat 2.0

Abstract: Omics tools provide broad data sets for biological discovery. However, the computational tools for identifying important genes or pathways in RNA seq, proteomics or GWAS data depend on GO annotations and are biased toward well-described pathways. This limits their utility as poorly annotated genes, which could have novel functions, are often passed over. Recently, we developed an annotation and category enrichment tool for Caenorhabditis elegans genomic data, WormCat, that provides an intuitive visualization o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…Nevertheless, having a single-entry point where GO annotations of any species can be accessed would be useful. Second, our website includes genes that are unannotated, which is often missing in gene function annotations and enrichment analyses [14]. Currently, extracting genes that are not annotated is not trivial and requires many steps that are different for each species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, having a single-entry point where GO annotations of any species can be accessed would be useful. Second, our website includes genes that are unannotated, which is often missing in gene function annotations and enrichment analyses [14]. Currently, extracting genes that are not annotated is not trivial and requires many steps that are different for each species.…”
Section: Resultsmentioning
confidence: 99%
“…But their output fields do not include publications or references that are linked to the evidence and require users to manually select output fields to conform to the GAF format. Second, our website includes genes that are unannotated, which are often missing in gene function annotations and enrichment analyses (Higgins et al, 2022). Currently, extracting genes that are not annotated requires many steps that differ across species.…”
Section: Discussionmentioning
confidence: 99%
“…In the alg-1 NDD mutants, a large proportion of proteincoding genes have been translationally perturbed, especially in the F180Δ and H751L mutants (9.0% of total protein-coding genes for F180Δ and 3.4% for H751L). Accordingly, we found that stress-related genes are significantly enriched in the translationally up-regulated genes in all four NDD mutants, suggesting that the perturbation of translatomes may be leading to proteome imbalance, which consequently triggers stress responses (Figure 9A, S7A) [49,50]. The F180Δ, G199S, and V254I mutants also exhibited up-regulation of small heat shock protein (HSP) genes, which encode chaperons that buffer insoluble protein aggregation [51] (Figure S7B), and the unfolded protein response (UPR)-related genes are also statistically enriched in the translationally up-regulated genes for all of the NDD mutants (Figure 9B), indicating that stress responses may be triggered by the misfolding and aggregation of proteins expressed at abnormally high levels in the mutants.…”
Section: Protein Homeostasis (Proteostasis) Is Tightly Controlled And...mentioning
confidence: 92%
“…A. MA plot of the translational levels of all protein-coding genes. Solid and text-labeled dots represent genes that are related to stress response [50].…”
Section: Bmentioning
confidence: 99%
“…Venn Diagrams were constructed by BioVenn 65 . WormCat analysis was performed using the website www.wormcat.com 27,66 and the whole genome annotation version 2 (v2) and indicated gene sets. PCA was conducted by using prcomp in R and graphed with ggplot in R studio.…”
Section: Methodsmentioning
confidence: 99%